Le rôle de la Programmation multi-objectif lexicographique dans le processus décisionnel : étude de cas à ABRAS: The role of lexicographic goals programming in the decision-making process : case study at ABRAS - YESLI Tynhinane (Journal of North African Economies, 2025)
The purpose of this article is to demonstrate the role and contribution of multi-objective programming in decision-making process. Thus we carried out a case study within the Algerian company ABRAS of ABRASIFS PRODUCTS where we applied the method of multi-objective linear programming on data for the year 2020. This method is considered to be one of the techniques that occupies an important place within the quantitative approach, given the great success it has achieved in terms of the number of problems dealt with, especially in the analysis and solving multiple, simultaneous and conflicting decision problems. The first results show that the Company will not be able to achieve at the same time, all the objectives initially established, but it has the possibility of achieving the highest priority objectives. As it has the possibility to revise its priority policy if necessary.